2022
DOI: 10.1136/bmjopen-2021-060540
|View full text |Cite
|
Sign up to set email alerts
|

Effects of multiple sclerosis on the audio-vestibular system: a systematic review

Abstract: ObjectiveSystematically investigate the effects of multiple sclerosis (MS) on the audio-vestibular system.MethodsSystematic review of literature investigating audio-vestibular conditions in persons with MS (PwMS) aged ≥18 years. PubMed, Scopus, NICE and Web of Science were searched. Randomised controlled trials, and cohort, case–control, observational and retrospective studies in English, published from 2000 to 21 November 2021, evaluated PwMS with at least one outcome (pure tone audiometry, auditory brainstem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…Of these, four articles analyzed OAE in patients with headache disorders (13)(14)(15)18), two studies evaluated patients with PD (8,9), and only two considered findings in MS. (7,16) We did not find any articles that analyzed OAE in patients affected by AD. The study exploring auditory function in patients with 'migraine' included a variety of migraine and headache subtypes: one study analyzed patients with vestibular migraine (13), one with cephalgic migraine (14), one study included both acephalgic and vestibular migraine patients (18), and one study analyzed auditory function in patients with tension-type headache (15).…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Of these, four articles analyzed OAE in patients with headache disorders (13)(14)(15)18), two studies evaluated patients with PD (8,9), and only two considered findings in MS. (7,16) We did not find any articles that analyzed OAE in patients affected by AD. The study exploring auditory function in patients with 'migraine' included a variety of migraine and headache subtypes: one study analyzed patients with vestibular migraine (13), one with cephalgic migraine (14), one study included both acephalgic and vestibular migraine patients (18), and one study analyzed auditory function in patients with tension-type headache (15).…”
Section: Resultsmentioning
confidence: 94%
“…Due to its high sensitivity, OAE can identify dysfunction of cochlear hair cells even in subclinical states ( 6 ). DPOAE is used to record auditory inner ear function in patients with neurological conditions ( 7–10 ). Accordingly, patients with MS ( 7 ), Parkinson’s disease (PD) ( 8 ), AD ( 9 ), and migraine ( 10 ) may show abnormalities in the test, reflecting OCH dysfunction, no unifying mechanism has yet been proposed to account for their abnormal DPOAE measures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies of vestibular function in MS have shown abnormalities in vestibular evoked potentials, electronystanography, static posturography ( 3 , 4 ) and dynamic visual acuity ( 5 ). Furthermore, worse vestibular function is associated with greater disability ( 6 ).…”
Section: Introductionmentioning
confidence: 99%